Combination RC4 Algorithm and Base64 Encryption on The Least Significant Bit Method - Soleman, Soleman; Budiman, Dendi; Mubaroq, Sefty (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2022)
Steganography is an art form of hiding data or information on a medium. Steganography was created as a way to secure data by hiding it in other media so that it is "invisible". In steganography, secret data is hidden in a carrier such as sound, image or video. Securing messages using steganography is still vulnerable to third parties because the message inserted is still the original message, so that when it is successfully deleted from the message carrier it can be immediately identified. Given these problems, the steganography method needs to be combined with other methods to strengthen the level of data security, in this case a combination of steganography and cryptography will be carried out so that the embedded message will be different from the original message. Even if the data is deleted from the user, the message cannot be known immediately. In this trial, the RC4 cryptographic method which has a symmetric key and also Base64 will be implemented in the PHP and Android programming languages using the Least Significant Bit (LSB) steganography method which will create encrypted secret messages embedded in JPG format, JPEG image media formats on each the last bit of a pixel so that the eye does not see the difference between the inserted and non-inserted images with the original image variable/result of 131.91KB after the Encryption process the amount of data is 31.92KB with very small differences so that data security is maintained without being visible to the naked eye